Vamsapriya yunnana, a new species of Vamsapriya (Xylariaceae, Xylariales) associated with bamboo from Yunnan, China - Jiang, Hong-Bo; Phookamsak, Rungtiwa; Bhat, Darbhe Jayarama; Khan, Sehroon; Bahkali, Ali; Elgorban, Abdallah; Hyde, Kevin (Phytotaxa, 2018)
Vamsapriya yunnana sp. nov., collected from dead bamboo in Yunnan Province of China, is described and illustrated in this paper. The new taxon is characterized by synnematous conidiophores, with enteroblastic, monotretic conidiogenous cells and brown to dark brown, 4–9-septate, fusiform conidia with a long, apical, appendage-like region. The species differs from the type and other species in the genus in having a wider fertile region and rostrate apex of the conidia. Maximum likelihood and Bayesian inference analyses of a combined ITS, LSU and RPB2 DNA sequence dataset show that V. yunnana is a new species, belonging to the genus Vamsapriya in Xylariaceae.